Romanian rurality within a modern conceptual model - Raluca, Ignat (Economics of Agriculture, 2010)
According to the Lisbon Declaration and to the necessity of growing Romanian economy competitiveness in knowledge based society, we consider requisite frontier research in agrifood field in order to lead to superior outputs of feld producers and traders and to adopt higher competitive behavior. Research demonstrates the opportunity of elaboration of a modern conceptual model for rural economy development: agrifood industrial city, able to provide economic growth of Romanian agrifood sector in knowledge based society. Also, the research reveals possibilities of higher life conditions. In order to demonstrate this, analysis and synthesis of studies, reports, articles and other materials including empirical studies and statistics on this topic were conducted.